KETIKA HIDUP DAN PEKERJAAN BERIRISAN: REFLEKSI KUALITATIF ATAS STRES KERJA SEBAGAI MEDIATOR DALAM PENINGKATAN KINERJA KARYAWAN - Nauli, Harum; Sitompul, Pandapotan; Irani Br Tarigan, Miska; Simangunsong, Ruben; Suriyani Sinaga, Irma (CV. Lafadz Jaya, 2025)
This study aims to illustrate how work stress mediates the intersection of personal and work life and employee performance. This intersection phenomenon is increasingly relevant in the modern, flexible yet demanding work environment, where the boundaries between domestic and professional life are often blurred. This study used a qualitative approach using in-depth interviews with employees from various work sectors. The findings indicate that deadline pressure, home-work role conflict, family disruptions during work, lack of rest time, and minimal supervisor support are the main factors triggering work stress. Although work stress is often associated negatively, the results of this study indicate that in some cases, stress can actually motivate employees to perform optimally, making it a complex mediating factor. Perceptions of stress vary depending on individual coping capacity and the supportive work environment. Coping strategies used include time management, social support, separation of work-personal space, and relaxation activities. This study concludes that work stress is not always a barrier but can be a bridge to improved performance when managed appropriately. These findings have important implications for company policies, HR management, and the development of an adaptive and healthy work culture.